Hepatoprotective and antioxidant activity of Persicaria maculosa aqueous extract against carbon tetrachloride induced hepatotoxicity in Wistar rats (Indian Journal of Traditional Knowledge (IJTK), 2023)
The consolidated hepatoprotective effect and antioxidant activity of Persicaria maculosa Gray were assessed against carbon tetrachloride (CCl4) instigated hepatic harm in Wistar albino rats. Aqueous extract of P. maculosa at a dosage of 400 mg kg-1. Every 14 days, a portion of one's body weight was administered orally. The generously raised serum marker catalysts for example, ALT, ALP, AST, total bilirubin and the cell reinforcement proteins, for instance, glutathione reductase, glutathione peroxidase, and glutathione-S-transferase were discovered as a result of CCl4 treatment. Following administration of plant extract, the levels of the previously mentioned enzymes were brought close to approaching regularity. At a dose of 100 mg/kg, silymarin was used as a standard reference drug in the study. The results of this study demonstrated unequivocally that Persicaria maculosa has a potent hepatoprotective effect in rats against CCl4-induced hepatic damage. Histopathological changes were also seen in livers of animals that received drugs. Simultaneous organization of silymarin altogether diminished the medications-induced biochemical and histological changes toward normalcy.